Modular multilevel DC-DC converters for HVDC grid interconnection - Saleh, Beeond M. (2022)
Since the introduction of voltage source converters, VSCs, which provide bidirectional power flow without reversing the DC voltage, high voltage direct current grids, HVDC girds, are becoming interest solution for expanding the existed ac grids. HVDC systems are preferred over the high voltage alternative current, HVAC, for long distance high power transmission due to lower total investment, lower power losses and HVDCs are technically and environmental superior. Additionally, they have been chosen as solutions for interconnecting off-grid communities, asynchronous AC grids and transmitting power from offshore winds. Because of the HVDC technology advantages and the absence of operational voltage standards, many point to point HVDC links have been established at different voltage levels. Developing these point to point HVDC systems to HVDC grids will require high voltage and high power DC-DC converters to interconnect different voltage levels and provide isolation.